A study of the major factors that contribute to employee loyalty in PP(T)SB / Muhammad Haris Ali Sifudin - Ali Sifudin, Muhammad Haris (2014)
The purpose of this study is to determine the major factor that contributes to employees loyalty in PETRONAS Penapisan Terengganu Sdn Bhd, PP(T)SB. Three factors were developed to describe which factors largely influence the level of employee loyalty. Data collected will assist researcher to determine the most factor that contribute to employee loyalty. Other purpose of this research is to determine the significant relationship between variables by using SPSS. Data will be analyzed on four tools including frequency analysis, reliability test, correlation and data descriptive statistic. 100 questionnaires have been distributed to the respondents but only 63 respondents return back the questionnaire. Result of the data show that most factor that contribute to employee loyalty is employee motivation with significant value of .393.